Pembrolizumab-Induced Mobitz Type 2 Second-Degree Atrioventricular Block - Alisha Khan; Sana Riaz; Robert Carhart (Case Reports in Cardiology)
Pembrolizumab is a monoclonal antibody directed towards programmed cell death protein 1 (PD-1) and is an antineoplastic drug which has a growing variety of oncologic uses. Pembrolizumab is commonly associated with immune-related adverse events (IRAEs) but is infrequently noted to cause cardiotoxicities such as myocarditis, arrhythmias, and heart failure. The following case report illustrates the clinical course of a 67-year-old female patient with stage IV non-small-cell lung cancer who developed Mobitz type 2 second-degree atrioventricular block three weeks after receiving her first infusion of pembrolizumab. Within a few hours of presentation, she progressed to symptomatic complete heart block requiring emergent placement of a temporary transvenous pacemaker. The article further discusses proposed mechanisms to explain IRAEs and management of IRAEs. We conclude by recommending a higher degree of caution and awareness among all physicians when treating patients on immunotherapy and a multidisciplinary approach when considering resumption of immune checkpoint inhibitor therapy.